ART SUBJECTS IN NATIONAL CURRICULA – IDEAS FOR FUTURE DEVELOPMENTS IN GENERAL EDUCATION - Sepp, Anu; Läänemets, Urve; Kalamees-Ruubel, Katrin; Kiilu, Kristi (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
International trends of globalisation, changing learning environments as well as particular socio-cultural contexts and educational policy making are constantly shaping selection of the content for national curricula (NC) of general comprehensive schools. Art subjects (music, literature and art education) have been compulsory elements in Estonian NC for a century already making a significant contribution to identity and personality development of all population. Traditionally, learning art subjects has been well supported by extra-curricular activities or hidden curriculum so far. Today, primarily due to changing cultures and new values, learning motivation and decline of reading and expressive skills of students have become an issue. A pilot research (students’ essays, n=367) was carried out in Estonian general comprehensive basic schools (level 3, students aged 13–16) in 2016 with the aim to specify how students perceive the role and meaning of art subjects in their life. The students’ interesting ideas and presented opinions deserve attention when designing syllabi in NCs as well as supportive learning environments for both formal and informal learning activities. Accordingly, an increasing role of art subjects in future curricula should be considered as integrative, balancing and enriching tools for socialization of each individual. Awareness of arts has the potential to contribute to cultural sensitivity and understanding – the meta-skills for future lifelong learning and sustainable developments.